THE EFFECT OF RISK-BASED INTERNAL AUDIT PLANNING AND COMPETENCE ON AUDIT QUALITY WITH THE INTERNAL AUDITOR PARADIGM AS A MODERATING VARIABLE - Nuke Nugraha; Helmi Yazid; Elvin Bastian (Jurnal Ekonomi, 2022)
The research was conducted to determine how much influence the risk-based planning of internal audits and competence on audit quality with the paradigm of internal auditors as a moderating variable. The object of the study was carried out at the Inspectorate General of the Ministry of Education and Culture of the Republic of Indonesia with the number of samples determined by 100 auditors. Data collection using questionnaires which were then analyzed using the SEM-PLS approach. The results of this study prove that good risk-based internal audit planning will achieve quality audit goals. In addition, auditors who have good competence will also affect the quality of audit results. The auditor paradigm has proven to moderate by weakening the role of competence on audit quality and strengthening the influence of risk-based internal audit planning on audit quality. This study concludes that good audit planning will achieve quality audit goals and an auditor with good competence will affect the quality of audit results.